Absorption Enhancement of Organic Solar Cell using Aluminum Oxide as a Photonic Crystal (Journal of Bangladesh Academy of Sciences, 2018)
Enhancement of light absorption in solar cell presents a strong challenge to its overall performance. We analyzed an Organic Solar Cell (OSC) with Photonic Crystal (PC) structure using Finite Difference Time Domain (FDTD) method. Aluminum oxide (Al2O3) has been used as photonic crystal structure and the lattice structure has been chosen to be hexagonal. Absorption enhancement has been observed by changing the height of the Hexagonal Lattice structure (HLS). When height is increased to 0.26 and radius to period ratio (r/a ratio) is set to 0.4, there is a significant increase of absorption in the middle wavelength region approximately from 463 nm to 575 nm and a significant decrease in lower wavelength. As the height is increased further, these changes in absorption begins to increase and at a certain value, these changes begin to reverse. Almost same phenomena occur when r/a ratio is 0.2 and 0.3 taken at approximately same height.Journal of Bangladesh Academy of Sciences, Vol. 42, No. 1, 87-97, 2018